Kelayakan Wacana Opini Kompas.id sebagai Sumber Belajar Keterampilan Menulis Teks Argumentasi di SMA - Hapsari, Fitria; Budiyono, Herman (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to describe the structure, linguistic features, and feasibility of opinion discourse published in Kompas.id as a learning resource for teaching argumentative writing skills in senior high school. The study employed a qualitative approach using content analysis within a discourse framework. The data consisted of 21 opinion texts from Kompas.id, selected through purposive sampling. The research instrument was an analysis card containing indicators of argumentative text structure, the use of factual and opinion sentences, and criteria for learning resource feasibility, including aspects of economy, practicality, relevance, positive values, and alignment with learning objectives. The findings indicate that most texts fulfill the basic structure of argumentative writing and consistently integrate factual and opinion statements in constructing logical reasoning. In terms of feasibility, 11 texts are categorized as highly feasible, 6 as feasible, and 4 as moderately feasible as learning resources. These findings provide an evaluative model for selecting digital opinion texts as instructional materials for teaching argumentative writing and support the strengthening of context-based Indonesian language learning.